Multichannel Broadcast Based on Home Channel for Cognitive Radio Sensor Networks - Fanzi Zeng; Yuting Tang; Jianjie Pu (The Scientific World Journal)
Considering the limited resources and the dynamic spectrum distribution in the cognitive radio sensor networks (CRSN), a half-duplex Multichannel broadcast protocol for CRSN is presented based on the home channel. This protocol maintains the networks topology only through the home channel, so there is no need for the public channel to transmit the control information and no need for the synchronization. After network initialization, node broadcasts data via home channel in half-duplex transmission way. The simulation results show that, compared with complete broadcast, the proposed protocol effectively reduces broadcast delay and overhead.